The Meranaw Lexical Variants and its Implication to the Standardization of Meranaw Orthography - Sharifa Khalid Masorong (Randwick International of Education and Linguistics Science Journal, 2021)
The language of the humankind is linked to the creation of meaning and expressions of human behaviors and emotions. Language is said to manipulate and persuade people’s perception of ‘reality’ (Holmes, 2013). The reality—social and linguistic landscapes— that people construct is affected by the linguistic choices members of the community make. This research investigated the possibility of a Meranaw uniform orthography in terms of the word spelling and symbols by examining the varieties of the language in terms of its lexicons. Understanding varieties can unlock answers questions regarding variety’s causes and its contribution to the development of the language in terms of orthography—which can actually help Meranaw writers extend studies on other components of the language. These factors contributed to the direction of this paper as it attempted to investigate the sprouting of the varieties and its lexical changes. The findings of the study revealed that even though there were Meranaw lexical variants, it does not hinder the communication to be effective. The paper also showed that Meranaw lexical variants are mutually intelligible among the surveyed Meranaw communities. Mutual intelligibility suggests that language is convention--- meaning that even if there are varieties, the Meranaw language itself serve as a unifying link in keeping a society intact. The Meranaw language brings together one culture and its usage is a means to express community’s style in an effort to create a social reality. This reality allows them to express their thoughts and ideas through their language